Experimental Study of Combined Nootropic Drugs on Glucose Levels During the Development of Hemic Hypoxia (Zien Journal of Social Sciences and Humanities, 2023)
Worldwide, according to statistics (WHO), 47.5 million people suffer from dementia, and 7.7 million new cases are detected every year. By 2050, the world is expected to have 140 million patients, that is, approximately three times more than today. “...Much of the increase is due to an increase in the number of people with dementia living in low- and middle-income countries...” Dementia is considered the main cause of disability among the elderly and senile people worldwide. Despite the availability of a large number of nootropic drugs with different mechanisms of action, they are mostly imported at high cost, are aimed at a specific mechanism for the development of hypoxia and dementia, and are not available to the middle and lower strata of the population. In this regard, one of the urgent tasks that meets the standards of today's medicine is the creation of new complex nootropic drugs with combined effects, the study of specific and toxicological characteristics, as well as the molecular mechanisms of antihypoxic action.